2001
DOI: 10.1073/pnas.041613098
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death mediated by ced-3 and ced-4 protects Caenorhabditis elegans from Salmonella typhimurium -mediated killing

Abstract: Programmed cell death (PCD) in mammals has been implicated in several disease states including cancer, autoimmune disease, and neurodegenerative disease. In Caenorhabditis elegans, PCD is a normal component of development. We find that Salmonella typhimurium colonization of the C. elegans intestine leads to an increased level of cell death in the worm gonad. S. typhimuriummediated germ-line cell death is not observed in C. elegans ced-3 and ced-4 mutants in which developmentally regulated cell death is blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(134 citation statements)
references
References 30 publications
4
127
1
2
Order By: Relevance
“…Factors such as the rates of apoptotic corpse-engulfment and germ cell proliferation, the precise age of the worm, and even the temperature have to be considered when reporting the number of germ cell corpses, ideally done as time course experiments. Also the possibility that bacterial contamination might trigger germ cell apoptosis has to be considered (Aballay and Ausubel 2001 ;Anton Gartner, unpublished observation). Methods for detecting germ cell corpses and for labelling them with GFP markers or speci fi c dyes have been described (Gartner et al 2004(Gartner et al , 2008 .…”
Section: Elegans Germ Cell Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as the rates of apoptotic corpse-engulfment and germ cell proliferation, the precise age of the worm, and even the temperature have to be considered when reporting the number of germ cell corpses, ideally done as time course experiments. Also the possibility that bacterial contamination might trigger germ cell apoptosis has to be considered (Aballay and Ausubel 2001 ;Anton Gartner, unpublished observation). Methods for detecting germ cell corpses and for labelling them with GFP markers or speci fi c dyes have been described (Gartner et al 2004(Gartner et al , 2008 .…”
Section: Elegans Germ Cell Apoptosismentioning
confidence: 99%
“…At present we know most about DNA damage response pathways leading to apoptosis. Finally, stresses such as starvation, heat shock, bacterial infection, or a high glucose diet also trigger excessive germ cell apoptosis (Salinas et al 2006 ;Angelo and Van Gilst 2009 ;Aballay and Ausubel 2001 ;Choi 2011 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that infection of C. elegans by the pathogenic bacterium Salmonella typhimurium induced cell death in the animal's germ line, and that these deaths were blocked in ced-3 or ced-4 mutant backgrounds. 37 Interestingly, these mutant animals were also more susceptible to Salmonella-mediated killing, even though the mutants' lifespans were not different from wild-type animals in the absence of infection. 37 It may be that the germline cell deaths observed in this infection model (or perhaps somatic cell deaths that remained undetected in the study) provide a measure of bacterial resistance to C. elegans.…”
Section: Elegans Caspasesmentioning
confidence: 93%
“…37 Interestingly, these mutant animals were also more susceptible to Salmonella-mediated killing, even though the mutants' lifespans were not different from wild-type animals in the absence of infection. 37 It may be that the germline cell deaths observed in this infection model (or perhaps somatic cell deaths that remained undetected in the study) provide a measure of bacterial resistance to C. elegans. An alternative but perhaps more intriguing possibility is that ced-3 function might be required for the activation of disease-resistance pathways in the soma, just as certain caspases are in higher metazoans (see below).…”
Section: Elegans Caspasesmentioning
confidence: 93%
“…Earlier studies have demonstrated that certain genes were induced against S. Typhimurium infection in Caenorhabditis elegans [6,7]. These studies fail to mimic the essential aspects of immunity induced by S. Typhi [8].…”
Section: Introductionmentioning
confidence: 98%